A modified two dimensional analytical model for short-channel fully depleted SOI MESFET's. (April 2018) - Mohammadi, Hossein; Abdullah, Huda; Dee, Chang Fu; Susthitha Menon, P.
Abstract: Analytical modeling of channel potential of SOI MESFET can be obtained by solving Poisson's equation to derive an expression for channel potential. Superposition method is an accurate technique for solving Poisson's equation, in which the solution of the 2-D Poisson's equation is represented as the sum of the 1-D Poisson's equation and a 2-D Laplace's equation solutions. In the existing models applying this method, the authors tried to solve 2-D Laplace's equation by using approximations [1] or modifying the boundary conditions [2] producing inaccurate results. In this report, a new methodology is applied to develop a modified analytical model for the channel potential of fully depleted SOI MESFET's, in which the drawbacks of the previous models are significantly eliminated. Using this model, the subthreshold performance of the device including channel potential, threshold voltage, drain current, and subthreshold swing under various conditions have been studied, plotted, and compared with TCAD simulation and experimental results. It is concluded the proposed model has been improved in term of accuracy compared to other existing models. Highlights: In this version of the article, the authors revised the manuscript according to the reviewers' comments including adding a verification chart to compare analytical (modelling) results with experimental data and extending the analytical investigation to cover more device parameters' range. The analytical results match very well with simulation data. The presented model displays the device performance for various device parameters and bias conditions.